Partial nephrectomy after selective embolization of tumor vessels in a hybrid operating room: A new approach of zero ischemia in renal surgery. Issue 2 (10th December 2015) - Bigot, Pierre; Bouvier, Antoine; Panayotopoulos, Paul; Aubé, Christophe; Azzouzi, Abdel Rahmène
Abstract : It is established that partial nephrectomy is the standard of care for tumors confined to the kidney. Achieving a partial nephrectomy without renal ischemia and limiting operative bleeding is the subject of numerous researches. Since 2010, hybrid operating rooms have been used to perform both interventional radiology and surgical procedures at the same place and time. We used this latest technology to treat 3 patients with localized kidney tumors. The tumors were of moderate complexity and all were treated after immediate hyperselective embolization by laparoscopic surgery without dissection and clamping of the renal pedicle. The embolization of tumor vessels could be performed using image‐stitching software. After embolization, operative time was 50, 70 and 80 minutes and blood loss was less than 100 ml for each case. Postoperative control 3D arteriography confirmed the respect of the vascularization of the healthy renal parenchyma. No postoperative complications occurred. Combined approach including hyperselective embolization and partial nephrectomy in the same time in a dedicated operating room is a new approach of zero ischemia during partial nephrectomy which reduces the difficulty of the surgery, limits injury to the kidney and increases patient safety. J. Surg. Oncol. 2016;113:135–137 . © 2015 Wiley Periodicals, Inc.